2016
DOI: 10.1038/npp.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Striatal Responses to Near-Miss Outcomes in Pathological Gamblers

Abstract: Near-misses in gambling games are losing events that come close to a win. Near-misses were previously shown to recruit reward-related brain regions including the ventral striatum, and to invigorate gambling behavior, supposedly by fostering an illusion of control. Given that pathological gamblers are particularly vulnerable to such cognitive illusions, their persistent gambling behavior might result from an amplified striatal sensitivity to near-misses. In addition, animal studies have shown that behavioral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 69 publications
(95 reference statements)
1
41
0
Order By: Relevance
“…In humans, mesolimbic circuits have also been implicated in this type of cognitive distortion, with heightened activity seen in cortical mesolimbic regions during near‐miss events in fMRI studies . Furthermore, these increases are greater in GD individuals compared with controls . These imaging studies also reported stronger striatal–insula connections when gamblers had higher illusions of control .…”
Section: Pathophysiologymentioning
confidence: 70%
See 1 more Smart Citation
“…In humans, mesolimbic circuits have also been implicated in this type of cognitive distortion, with heightened activity seen in cortical mesolimbic regions during near‐miss events in fMRI studies . Furthermore, these increases are greater in GD individuals compared with controls . These imaging studies also reported stronger striatal–insula connections when gamblers had higher illusions of control .…”
Section: Pathophysiologymentioning
confidence: 70%
“…179,180,185 Furthermore, these increases are greater in GD individuals compared with controls. 186 These imaging studies also reported stronger striatal-insula connections when gamblers had higher illusions of control. 187 Finally, the insula has also been strongly implicated in the processing of near-miss events.…”
Section: Cognitive Distortionsmentioning
confidence: 86%
“…A total of 177 pathological gamblers (PGs) and 169 healthy controls (HCs) were included in the present study. These data were pooled from nine separate previous neuroimaging studies 8,15,18,[43][44][45][46][47][48] (Supplementary Table 1). From this aggregated sample, 18 participants (10 PGs and 8 HCs) were excluded because of head movement artefacts on anatomical T1 scans preventing us from reliably identifying OFC sulcogyral patterns, and 4 participants (2 PGs and 2 HCs) were excluded because either demographic or diagnostic information was missing.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…For example, near-wins (loss events perceptually close to the jackpot; e.g., two dollar signs and a cherry aligned on the display of a slot machine) exert rewarding effects (Clark, Crooks, Clarke, Aitken, & Dunn, 2012; Clark, Lawrence, Astley-Jones, & Gray, 2009). Abnormal reaction to near-wins correlate with GDPs’ beliefs on the mastery of their instrumental or predictive skills, and, at the neurobiological level, is associated to BOLD signal in the ventral striatum, comparable to the one caused by true wins (Chase & Clark, 2010; Habib & Dixon, 2010; Sescousse et al., in press). In other words, up-regulating positive emotions could contribute, not only to gambling expectancies, but also to alter the mechanisms responsible for learning about appetitive aspects of gambling outcomes via, again, associative learning and causal attribution mechanisms.…”
Section: Introductionmentioning
confidence: 99%